RMS Modeling and Control of a Grid-Forming E-STATCOM for Power System Stability in Isolated Grids - José Luis Rodriguez-Amenedo; Miguel E. Montilla-DJesus; Santiago Arnaltes; Francisco Arredondo (Applied Sciences)
This paper presents a comprehensive RMS-based phasorial model of an E-STATCOM with grid-forming (GFM) control, designed to improve power system stability in isolated grids. Unlike previous approaches, this model integrates a governor with an internal power system stabilizer (PSS) and an active current limiter (ACL) to enhance frequency regulation and mitigate oscillations. Additionally, an exciter with a nonlinear modulation function is introduced to optimize voltage regulation and reactive power support. A detailed conventional supercapacitor (SC) model is also incorporated, enabling dynamic DC-voltage control based on active power variations, improving frequency stability. The proposed E-STATCOM RMS model includes algebraic equations, dynamic governor and exciter models, supercapacitor-based energy storage control, and an advanced current-limiting strategy. Simulations are conducted on the Fuerteventura–Lanzarote (Canary Islands, Spain) power system, comparing the E-STATCOM with a synchronous condenser (SynCon) in frequency response, voltage regulation, and fault performance. The results show that the E-STATCOM improves frequency stabilization and energy efficiency while complying with grid codes. This study introduces a novel RMS-based modeling approach for GFM E-STATCOMs, bridging the gap between theoretical phasorial analysis and real-world applications. The findings confirm that E-STATCOMs are a viable alternative to SynCons, enhancing grid stability in high-renewable-penetration systems.